Proceedings of the 28th Annual ACM Symposium on Applied Computing 2013
DOI: 10.1145/2480362.2480537
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of state-of-the-art features for microblog search

Abstract: We investigate in this paper information retrieval in microblogs exploiting different state-of-the-art features. Microbloggers, besides posting microblogs, search for fresh and relevant information related to their interests, by submitting a query to a microblog search engine. The majority of approaches that collect information from microblogs exploit features such as the recency of the microblog, the authority of his/her author. . . to improve the quality of their results. In this paper, we evaluated some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…Huurdeman, Kamps, Koolen, and Wees (2012) have exploited the number of reviews, the rating average and the user tag frequencies in the social information retrieval. Damak, Pinel-Sauvagnat, Boughanem, and Cabanac (2013) have introduced the language quality and Badache, & Boughanem, (2015) have exploited social signals such as the number of user likes and shares.…”
Section: Related Workmentioning
confidence: 99%
“…Huurdeman, Kamps, Koolen, and Wees (2012) have exploited the number of reviews, the rating average and the user tag frequencies in the social information retrieval. Damak, Pinel-Sauvagnat, Boughanem, and Cabanac (2013) have introduced the language quality and Badache, & Boughanem, (2015) have exploited social signals such as the number of user likes and shares.…”
Section: Related Workmentioning
confidence: 99%
“…These different features present challenges as well as new opportunities to microblog search engines. Several previous studies have tried combining some of these features to form a better ranking algorithm for microblogs [8,10,11], usually with the help of machine learning. For example, Damak et al's study [8] found that tweet popularity, length, exact term matching, URL presence, URL popularity in the corpus, URL frequency in the microblog and the recency of the microblog were the best relevance indicators.…”
Section: Related Workmentioning
confidence: 99%
“…However, the distinct features of microblogs as well as the sheer amount of them bring significant challenges to tools that aim to efficiently and effectively mine useful information from these messages. Microblog messages differ from conventional Web pages in various aspects [8]. Furthermore, people look for different things in microblogs and search in different ways [9].…”
Section: Introductionmentioning
confidence: 99%
“…• Similarity of content [8] In our case, it measures how many tweet of the whole conversation C are similar in content with current tweet t current . We calculate cosine similarity score for every pair of tweets.…”
Section: Text-based Signalsmentioning
confidence: 99%